Gestión Administrativa y la Optimización de los Recursos Financieros en el Consorcio Chuchum - Macas Loaiza, Liwenth Halmantt (2017)
onsorcio Chuchum is constituted on May 23, 2016; as a result of the temporary union of two companies to carry out mining works in the Chuchumbletza area, Canton Yanzatza. (Reyes, 2017) It states that: "Experience teaches us and sociological studies are responsible for justifying this appreciation that man is grouped in society, mainly because of its insufficiency to achieve all its ends alone" (p4). (Bermúdez & Rodríguez, 2013) point out that "the problem is the question of which some data are known, which must be handled conveniently to find another one that is sought" (p69). This research seeks to identify the critical problem that is evident; due to the administrative management model that is a sub-line of research of the Technical University of Babahoyo; achieving in this way to increase the production and reach the point of balance that allows to support the commercial operations of the Consortium, improving the processes of control of management of the financial resources of the company